2018
DOI: 10.1159/000495840
|View full text |Cite
|
Sign up to set email alerts
|

Cell Type-Specific Gene Expression of Alpha 5 Subunit-Containing Gamma-Aminobutyric Acid Subtype A Receptors in Human and Mouse Frontal Cortex

Abstract: Converging evidence suggests that deficits in somatostatin (SST)-expressing neuron signaling contributes to major depressive disorder. Preclinical studies show that enhancing this signaling, specifically at α5 subunit-containing γ-ami­nobutyric acid subtype A receptors (α5-GABAARs), provides a potential means to overcome low SST neuron function. The cortical microcircuit comprises multiple subtypes of inhibitory γ-aminobutyric acid (GABA) neurons and excitatory pyramidal cells (PYCs). In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 41 publications
2
21
0
Order By: Relevance
“…For instance, we observed that the spatial pattern of [ 11 C]Ro15-4513 binding covaried most strongly with a gene cluster containing GABRA5, GABRA2 and SST. This finding is consistent with preclinical literature showing that GABAARα5 are enriched on principal cell membranes targeted by SST cells (5,26,40). Moreover, [ 11 C]Ro15-4513 has been shown to present 10-15-fold higher affinity to human cloned GABAARα5 than to GABAARα1-3 (23) and the co-expression of GABRA2 and GABRA5 was previously shown by immunohistochemistry in the rat brain (16), which we observed in our analyses as well.…”
Section: Discussionsupporting
confidence: 93%
“…For instance, we observed that the spatial pattern of [ 11 C]Ro15-4513 binding covaried most strongly with a gene cluster containing GABRA5, GABRA2 and SST. This finding is consistent with preclinical literature showing that GABAARα5 are enriched on principal cell membranes targeted by SST cells (5,26,40). Moreover, [ 11 C]Ro15-4513 has been shown to present 10-15-fold higher affinity to human cloned GABAARα5 than to GABAARα1-3 (23) and the co-expression of GABRA2 and GABRA5 was previously shown by immunohistochemistry in the rat brain (16), which we observed in our analyses as well.…”
Section: Discussionsupporting
confidence: 93%
“…In the cortex, pyramidal cells exhibit dendritically localized α5 GABA A Rs at sites innervated by bitufted interneurons (an SST positive neuron class; Ali and Thomson, 2008). A recent human and mouse prefrontal cortex gene expression study determined that the majority of α5 GABA A Rs are in pyramidal cells, followed by parvalbumin interneurons (Hu et al, 2018). Interestingly, α5 GABA A R mRNA was uniquely expressed in human SST interneurons, albeit at a low level.…”
Section: Cellular and Circuit Localizationmentioning
confidence: 99%
“…GABA neurons shape this activity differently based on non-overlapping populations that co-express SST, the calcium-binding protein parvalbumin (PV+), or the ionotropic serotonin receptor 5HT3aR with or without vasoactive intestinal peptide (VIP+) (Rudy et al, 2011). SST+ cells gate excitatory PN input via dendritic inhibition and modulate output via perisomatic disinhibition through SST-PV+ cell afferents (Fee et al, 2017;Hu et al, 2019). Dendritic SST+ cell inhibition is partially mediated by GABA acting on GABA-A and GABA-B receptors (GABAA-R/GABAB-R) (Urban-Ciecko et al, 2015;Schulz et al, 2018), whereas the SST peptide is released under distinct firing conditions (Katona et al, 2014;Yavorska and Wehr, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The regional and functional differentiation of GABAA-Rs depend upon heteropentameric subunit composition, commonly containing two α, two β, and one γ-subunit (Rudolph et al, 2001;Sieghart and Sperk, 2002). SST+ cell functions are partially mediated by a5 subunit-containing-GABAA-Rs given their localization to PN dendrites and PV+ cells in the PFC, hippocampus (HPC), and ventral striatum (Ali and Thomson, 2008;Schulz et al, 2018;Hu et al, 2019). GABRA5 transcripts, encoding α5GABAA-Rs, were also reduced in the PFC of MDD and aged subjects (Oh et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation